ANALISIS PEMBELIAN IKAN SEGAR DAN IKAN OLAHAN PADA IBU BEKERJA DAN IBU TIDAK BEKERJA - Karuniawati, Tevi; Satria, Arif; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
This research aimed to analyze the factors that influence fresh and processed fish purchasing of working mothers and housewives in Bogor City, West Java. This research involved 200 peoples that were selected purposively. Data were collected by interview and were analyzed by conjoint, Fishbein, and Logit analysis. The result showed that both working mothers and housewives more concerned about fish condition rather than fish types. The knowledge about content, type, and processing of fish of both working mothers and housewives were relatively similar. The attitude of both working mothers and housewives was same. Both of them prefer fresh fish rather than processed fish. Purchasing of fresh and processed fish was measured by the frequency and quantity of purchasing. The factors that affect the frequency of fresh fish purchasing were family expenditure, preference, and knowledge, while the frequency of processed fish purchasing was influenced by education, family size, and attitude. Furthermore, the factors that affect the quantity of fresh fish purchasing were family expenditure, while the quantity of processed fish purchasing was influenced by family size.